2014
DOI: 10.1002/ajpa.22555
|View full text |Cite
|
Sign up to set email alerts
|

Stable isotopes complement focal individual observations and confirm dietary variability in reddish–gray mouse lemurs (Microcebusgriseorufus) from southwesternMadagascar

Abstract: We examine the ecology of reddish-gray mouse lemurs from three habitats at Beza Mahafaly Special Reserve using focal follows and stable carbon and nitrogen isotope data. Focal observations indicate dietary differences among habitats as well as sexes and seasons. Both sexes consume more arthropods during the rainy season but overall, females consume more sugar-rich exudates and fruit than males, and individuals from riparian forest consume fewer arthropods and more fruit than those in xeric or dry forest. We as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 50 publications
0
33
0
1
Order By: Relevance
“…Because tissues used for stable isotope analyses (e.g., hair, teeth, and bone) reliably record the nature of isotopic intake, isotope ecology has recently gained popularity in primatological research (Crowley, Rasoazanabary, & Godfrey, ; Oelze et al, ; Sandberg, Loudon, & Sponheimer, ; Schoeninger, ; Schoeninger, Iwaniec, & Nash, ). Furthermore, a particular advantage of using δ 13 C and δ 15 N as dietary indicators is the possibility to incorporate otherwise unobtainable data on groups unhabituated to researcher presence in the face of rapid species decline (e.g., Kühl et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because tissues used for stable isotope analyses (e.g., hair, teeth, and bone) reliably record the nature of isotopic intake, isotope ecology has recently gained popularity in primatological research (Crowley, Rasoazanabary, & Godfrey, ; Oelze et al, ; Sandberg, Loudon, & Sponheimer, ; Schoeninger, ; Schoeninger, Iwaniec, & Nash, ). Furthermore, a particular advantage of using δ 13 C and δ 15 N as dietary indicators is the possibility to incorporate otherwise unobtainable data on groups unhabituated to researcher presence in the face of rapid species decline (e.g., Kühl et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, in larger‐scale comparisons of δ 13 C and δ 15 N values across multiple ecological conditions potential conclusions become less straightforward. Initial studies attempted to evaluate aspects of primate diet and ecology using tissue samples alone, yet the recognition of the variability of tropical ecosystems led researchers to embrace the incorporation of environmental context into cross‐site comparisons (Crowley et al, ; Oelze et al, ; Oelze et al, ). For example, one prominent contextual measure of isotope system variability was mean annual precipitation (MAP).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, every location should have a unique plant isotope baseline. Recently, Crowley and colleagues (Crowley et al, 2014) suggested calculation of a mean isotope ratio of a standardized vegetation sample (e.g. only C3, non-leguminous plants)…”
mentioning
confidence: 99%
“…A look through the major journals in 2014 shows the diversity of field and study contexts in which biological anthropologists are embedded. For example, a single issue of the American Journal of Physical Anthropology (September 2014) includes the following: articles describing primate biology in Ethiopia (Fashing et al ), Madagascar (Crowley et al ), and the Philippines (Smith et al ); articles investigating the relationships of historic and prehistoric human populations in southern Africa (Irish et al ) and Southeast Asia (Matsumura and Oxenham ); articles looking at issues of health or developmental biology in prehistoric Aboriginal Australians (Durband ), Irish famine victims (Geber ), French Neandertals (Garralda et al ), Dutch children (Vucic et al ), and Kenyan pastoralists (Iannotti and Lesogorol ); articles examining biomechanical issues in skeletal material from southern South America (Menéndez et al ), Romania (Webb et al ), and medieval France (Le Luyer et al ). …”
Section: Into Ancestry and Racementioning
confidence: 99%